A business case or social responsibility? How top managers' support for work-life arrangements relates to the national context. Issue 5 (20th October 2017) - Been, W. M.; den Dulk, L.; van der Lippe, T.
ABSTRACT: The extent to which organizations supplement statutory work-life arrangements varies systematically between countries. Empirical evidence on how organizations' approaches to work-life arrangements relate to the national context is, however, mixed. This study aims to elucidate this complex relationship by focusing on how top managers' considerations about whether or not to provide work-life arrangements are related to the national context. Semi-structured interviews were held with 78 top managers in Finland, the Netherlands, Portugal, Slovenia and the UK. This study finds that top managers' relate their considerations whether to provide work-life arrangements to the extensiveness of national legislation: only in the context of few state work-life policies top managers saw it as a business issue. Top managers also take into consideration what they believe is expected of them by employees and society at large, which can work either in favor or against the provision of work-life arrangements. Perceiving the provision of work-life arrangements as a social responsibility seems more apparent for top managers in Slovenia and Finland. By leaving the social responsibility argument out of the central framework of most studies, the existing literature appears to tell the story mainly from an Anglo-Saxon perspective placing business oriented arguments central.